2005
DOI: 10.1063/1.1883325
|View full text |Cite
|
Sign up to set email alerts
|

Optical response of a ferromagnetic-diluted magnetic semiconductor hybrid structure

Abstract: We investigate the possibility of using local magnetic fields to produce one-dimensional traps in hybrid structures for any quasiparticle possessing spin degree of freedom. We consider a system composed of a diluted magnetic semiconductor quantum well buried below a micron-sized ferromagnetic island. Localized magnetic field is produced by a rectangular ferromagnet in close proximity of a single domain phase. We make quantitative predictions for the optical response of the system as a function of distance betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…We note that our calculated valence band offsets for CdTe/MgTe (0.75 eV), CdTe/Cd 0.65 Mg 0.35 Te (0.26 eV) agree with those given in Refs. [37] and [38] respectively. Note that this later is given for …”
Section: Cdmgtementioning
confidence: 99%
“…We note that our calculated valence band offsets for CdTe/MgTe (0.75 eV), CdTe/Cd 0.65 Mg 0.35 Te (0.26 eV) agree with those given in Refs. [37] and [38] respectively. Note that this later is given for …”
Section: Cdmgtementioning
confidence: 99%
“…Resistivity measurements have also been done in DMS Ge 1 À x Mn x showing metal-insulator transition down to 18 K [5]. Fabrication and characterization of bulk and thin films of Mn-doped Ge DMS with various doping levels of Mn have been carried out by researchers [4][5][6][7][8][9]. Electrical and magnetic properties have been extensively studied in these Ge based DMS materials.…”
Section: Introductionmentioning
confidence: 99%
“…Good quality single crystals of Ge 1À x Mn x (0oxo0.1) were grown using Bridgman's crystal growth technique and studied by Kang et al [14]. These works [4][5][6][7][8][9][10][11][12][13][14] reveal the fact that the preparation of homogeneous Ge 1À x Mn x DMS samples is very difficult and it was found that strong phase separation exists with dominant phases such as Mn-poor Ge 8 Mn 11 and Mn-rich Ge 3 Mn 5 . Beigger et al [15] compared the magnetic data of Ge 1 À x Mn x with other phases like Ge 8 Mn 11 and Ge 3 Mn 5 and observed that there was a strong ferromagnetic behavior in Ge 1À x Mn x which arises mainly due to phase separated Mn-rich domain Ge 3 Mn 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a challenge because most magnetic semiconductors lose their magnetic properties at temperatures near room temperature and would require expensive and impractical refrigeration in order to work in actual computer. These developments have induced researchers to grow and characterize some of the DMS materials using both forms single crystals and thin films [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%